The Economies of Scope in Agricultural Productions: A Case of Jogjakarta Province - Mariyono, Joko; Pawukir, Enny Suswati (TEMA, 2003)
The objective of this study is to identify the performance of regional productions of rice and soybean that have been jointly cultivated during a year at the same irrigated lands. The study is motivated by the fact that decentralisation of governments has been implemented, and consequently the local resources possessed by local region need to be exploited economically. This study uses the concept of economies of scope as underpinning theory. Pooled estimation is used for estimating product transformation curve that describes the relationship between soybean and rice productions. Data consisting of four districts and eleven years used in this analysis is collected from publication of local statistical offices. The results of study indicate that yearly joint production of rice and soybean shows degree of economies of scope, implying that the level of joint products is physically higher than that of separated product. However, under given market prices, the profitability of joint productions is economically low, compared with single production of rice. This is because yield of soybean is low, and the relative price of soybean is not too high. It is therefore, in this case, more money-making to grow rice as much as possible in the irrigated lands. Keywords: economies of scope, product transformation curve, rice and soybean